Project management for healthcare - Shirley, David L., 1948- (Boca Raton : CRC Press, 2020)
Project Management for Healthcare, Second Edition covers the significant changes in both the direction of healthcare and the direction of project management. The most significant change in healthcare is the prevalence of online data and the need for its protection. The book explains how data can be protected during a project's lifecycle. The most significant change in project management is Agile, and a new chapter covers how Agile can be applied to projects in healthcare. This new edition also covers green technology and sustainability. Exploring the discipline of project management from the perspective of the healthcare, the book dissects the project process and covers the management skills required to successfully manage a project. By defining a project to include the tools and techniques required, the book shows how to successfully deliver a project from identifying stakeholders and developing and gaining consensus on requirements to constructing a project plan. It also covers in detail the skills required to successfully manage project stakeholders and team members. At times, healthcare personnel may have to work with program management, or may even be part of program management and must interact with pharmaceutical companies and medical device manufacturers. This book covers program management and how it relates to the healthcare industry and some of the project processes used by those companies involved in pharmaceuticals and manufacturers of medical devices. By giving an inside look at the processes used, the book gives an understanding of how those companies bring their products to market and how to adapt those processes for their own benefit. Managing healthcare projects using the discipline of project management is a skill that can help healthcare professionals better utilize limited resources, both human and monetary, and ensure the highest possible quality of care to meet or exceed their stakeholders' expectations. Project Management for Healthcare, Second Edition shows how to use the discipline of project management to achieve those goals successfully.
OCLC-licensed vendor bibliographic record.
Keywords: Health services administration; Project management; BUSINESS & ECONOMICS / Industries / Service Industries; BUSINESS & ECONOMICS / Project Management; COMPUTERS / Information Technology